Common cardiac comorbidities and perioperative assessment modalities for liver transplant candidates – an update - F. Hackl; A. V. Kopylov; M. D. Kaufman (Трансплантология (Москва))
Cardiac complications are currently the leading cause of early mortality following liver transplantation. Guidelines for the cardiac workup prior liver transplantation are limited. In this review we are discussing commonly modalities used for cardiovascular evaluation of liver transplant candidates.Authors declare no conflict of interest.